TINDAKAN SOSIAL DAN PEMILIHAN MODEL JILBAB DI KELURAHAN SIMPANG BELUTU KECAMATAN KANDIS - Susan Dewi; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The development of hijab fashion experienced significant improvement. The presence of hijab fashion changes some of the people from identical hijab that is not pretty and old fashioned to shift meaning is common for the people. The presence of various hijab models became an attraction for women, especially the women in Simpang Belutu Village. The selection of hijab models in the Simpang Belutu Village has a varienty of objectives, from the goals produce different action for women in using the model of hijab. From these goals teh researcher wants to look at women in the Simang Belutu Village in Kandis District. The existence of the phenomenon researchers is interested to research the phenomenon with title is SOCIAL ACTION AND THE SELECTION OF MODELS OF HIJAB IN THE SIMPANG BELUTU VILLAGE KANDIS DISTRICT. This research use qulaitative method with descriptive analysis and use purposive sampling technique of data collection was inteview, observation and documention and used primary and secondary data sources. From the results of the research obtained from five informants, it can be concuded that there were two models of hijab that dominate on women in the location, taht are the model of the syar’i hijab and the model of rectangukler hijab. There are the goals to be achieved from the selection of hijab models was undertaken, so that from the result finding of the field the researcher conclude the goals in three social action, that is rational instrumental action, rational value values and traditional action. From same of these goals it found taht afshion hijab greatly influences selection the hijab models which exists in the location, because from the five informants almost all follows the development of exixting hijab fashion.Keywords : Social Action, Hijab Models Selection